2005
DOI: 10.1038/sj.gene.6364182
|View full text |Cite
|
Sign up to set email alerts
|

Risk of trachomatous scarring and trichiasis in Gambians varies with SNP haplotypes at the interferon-gamma and interleukin-10 loci

Abstract: Experimental evidence implicates interferon gamma (IFNg) in protection from and resolution of chlamydial infection. Conversely, interleukin 10 (IL10) is associated with susceptibility and persistence of infection and pathology. We studied genetic variation within the IL10 and IFNg loci in relation to the risk of developing severe complications of human ocular Chlamydia trachomatis infection. A total of 651 Gambian subjects with scarring trachoma, of whom 307 also had potentially blinding trichiasis and pair-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 57 publications
1
40
1
1
Order By: Relevance
“…[11][12]14,16,17 Quantitative association between IL-10 À1082 SNP polymorphism and IL-10 production has been previously demonstrated by unspecific stimulation of lymphocytes with LPS or ConA, 18 but the role of IL-10 counteracting antigen-specific CMI responses has remained unclear. In this study, we demonstrated that IL-10 À1082 SNP is linked to IL-10 secretion as well as to interaction between in vitro infected monocytes and antigen-specific T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12]14,16,17 Quantitative association between IL-10 À1082 SNP polymorphism and IL-10 production has been previously demonstrated by unspecific stimulation of lymphocytes with LPS or ConA, 18 but the role of IL-10 counteracting antigen-specific CMI responses has remained unclear. In this study, we demonstrated that IL-10 À1082 SNP is linked to IL-10 secretion as well as to interaction between in vitro infected monocytes and antigen-specific T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported previously disease associations at the IFNg, IL10 and MMP9 loci in these subjects. 41,42 The study and its procedures were approved by the Gambia Government/MRC Ethics Committee (SCC 729/857), the Ethics committees of the London School of Hygiene and Tropical Medicine and of Oxford University, and are in accordance with the Declaration of Helsinki. Subjects diagnosed with trichiasis were offered free corrective surgery.…”
Section: Subjectsmentioning
confidence: 99%
“…Genotypes were determined by the Sequenom system using matrix assisted laser desorption/ionization time-of-flight (MAL-DI-TOF) mass spectrometry as described previously. 41 Primer sequences are available on request.…”
Section: Dna Extraction and Snp Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In trachoma, several host inflammatory response genes have been identified as contributing to the severity of fibrotic disease leading to conjunctival scarring and trichiasis (turning-in of the eyelashes). [39][40][41] For example, part of the host immune system's initial defense against C. trachomatis infection is the activation and cytotoxic response of natural …”
Section: Host Factorsmentioning
confidence: 99%